Analisis Big Data Google Trends: Perspektif Pariwisata dan Pekerja Migran di Provinsi Bali Tahun 2022 - Anasya, Hadisha Shafa; Purwoto, Agus; Maulina, Hersa; Mangiwa, Romario Desouza D.; Sari, Seli Delima (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Bali, known as the "Island of the Gods," is a popular tourist destination with natural beauty, rich culture, and the hospitality of the local people which form the backbone of the region's economy through the tourism sector. The year 2022 was crucial for Bali to recover its tourism sector, which was impacted by the COVID-19 pandemic, while facing challenges of changing worker migration patterns due to travel restrictions and global economic changes. This study aims to understand global public interest in tourism and search trends related to tourism, as well as migrant worker interest in Bali Province, using Google Trends analysis. The analysis was conducted using the accumulated searches for the keywords 'Bali' and 'Jobs Bali,' sorted by the countries whose residents searched for these keywords the most on Google Trends. The results show that interest in Bali as a tourist destination mostly comes from European countries, while searches for the keyword "Jobs Bali" are mostly conducted from Australia. The search trend for "Bali" increased throughout 2022, while searches for "Jobs Bali" tended to fluctuate. These findings indicate that the dissemination of information about tourism and employment opportunities in Bali Province is still uneven in several countries, necessitating the government to strengthen management and marketing strategies to revive the tourism and economy sectors in Bali Province.